Psychological Capital As A Coping Resource Against Technostress In The Age Of AI: A Study Of Employees At Private Sector Banks In Mumbai (The Review of Diabetic Studies, 2025)
Technostress has emerged as a modern occupational hazard, particularly within high-tech sectors such as banking, where digitalization and AI integration are accelerating. AI exposure is not neutral, it becomes a source of cognitive and emotional strain, increasing the importance of coping resources like psychological capital. Psychological Capital (PsyCap) comprising hope, efficacy, resilience, and optimism has been identified as a key internal resource that can empower employees to cope with change. In this perspective, the study’s major objectives were to examine the level and effect of technostress experienced by employees in private sector banks in the context of AI integration, to assess the role of Psychological Capital (PsyCap) as a coping resource influencing the relationship between technostress and employee well-being and to examine the effects of demographic variables on employees' coping mechanisms, psychological capital, and technostress in private sector banks. A conceptual model was developed to test the impact of technostress on employee coping and well-being, while incorporating PsyCap as a key psychological variable. The research utilizes an exploratory and descriptive design, utilizing both quantitative and qualitative methodologies to gain a comprehensive understanding of the subject. A structured questionnaire was administered to 100 employees of private sector banks in Mumbai, India who regularly use AI-enabled tools and are exposed to technostress in their job roles. The relationship between Psychological Capital and Employee Well-being in private sector banks was tested using Chi Square test. The findings revealed that higher levels of technostress negatively impact employee well-being; however, individuals with stronger PsyCap report better coping outcomes. Particularly, PsyCap moderated the adverse effects of technostress, particularly in high-AI-use departments, highlighting its protective role in AI-intensive environments. This study offers significant implications for HR professionals and organizational leaders aiming to foster employee resilience and adaptability amid technological disruption. By investing in the development of PsyCap through targeted interventions, banks can not only reduce technostress but also promote sustainable employee well-being in the AI-driven workplace.